Eugenics and the playground movement. Issue 2 (15th March 2018) - Mobily, Kenneth E.
ABSTRACT: The purpose of this study was to scrutinize the Playground Movement through the lens of eugenics. The theoretical relationship was clear because of the dominant influence of inheritance-driven theories that stressed the role of play in developing desirable traits. Progressive Era emphasis on race betterment provided an optimal environment for the use of eugenic practices to correct flawed members of society; the emphasis on guided play satisfied this need. Playground leaders were also challenged by threats to its credibility from sequestration measures – ugly laws and discrimination. This forced them to defend play using instrumental definitions and caused them to acquiesce to segregated arrangements for the defective and diverse of society at times. Eugenic-like strategies were reflected in trying to normalize development of children through retracing the evolutionary trail of the race, altering future generations' DNA profile, and as an attempt to repair the faults and failings of the current generation.